Antidepressant medication during pregnancy and epigenetic changes in umbilical cord blood: a systematic review. Issue 1 (December 2016) - Viuff, Anne-Cathrine; Pedersen, Lars; Kyng, Kasper; Staunstrup, Nicklas; Børglum, Anders; Henriksen, Tine
Abstract Introduction Epigenetic mechanisms are important for the regulation of gene expression and differentiation in the fetus and the newborn child. Symptoms of maternal depression and antidepressant use affects up to 20 % of pregnant women, and may lead to epigenetic changes with life-long impact on child health. The aim of this review is to investigate whether there is an association between exposure to maternal antidepressants during pregnancy and epigenetic changes in the newborn. Material and methods Systematic literature searches were performed in MEDLINE and EMBASE combining MeSH terms covering epigenetic changes, use of antidepressant medication, pregnancy and newborns. A keyword search was also performed. We included studies on pregnant women and their children where there was a history of maternal depressed mood or anxiety, a reported use of antidepressant medication, and measurements of epigenetic changes in umbilical cord blood. Studies using genome-wide or candidate-based epigenetic analyses were included. Citations and references from the included articles were investigated to locate further relevant articles. The completeness of reporting as well as the risk of bias and confounding was assessed. Results Six studies were included. They all investigated methylation changes. Genome-wide methylation changes were examined in 184 children and methylation status in specific genes was examined in 96 children exposed to antidepressant medication. Three of the studies found an association between use of antidepressant medication during pregnancy and methylation status at various CpG sites measured in cord blood of the newborn. One of these studies found an association in African-Americans, but not Caucasians. The remaining three studies found associations between maternal mood and epigenetic changes in umbilical cord blood but no association between epigenetic changes and maternal use of antidepressant medication. Conclusion The included studies have not established a clear association between use of antidepressant medication during pregnancy and epigenetic changes in the cord blood. Future studies using newer, more wide-ranging epigenetic methods could discover possible new differentially methylated sites. Larger sample sizes and good validity of exposures are warranted in order to adjust for level of maternal depression, other maternal illness, maternal use of other types of medication, and maternal ethnicity. PROSPERO registration number: CRD42015026575.